Analysis of Residential Property Market Value Using Market and Cost Approach - Binti Miftakhul Jannah; Aang Afandi; Rosy Aprieza Puspita Zandra (Jurnal Akuntansi Bisnis dan Humaniora, 2023)
Banks require guarantees as a benchmark for lending and alternative payments when there is a bottleneck in credit payments. This research aims to determine the market value of residential property in the form of a house which is used as a basis for guaranteeing debt in the Malang City area. The market value is obtained with a market approach using a market data comparison method and a cost approach with a market data comparison method to find land market values ​​and the depreciated replacement cost method to find building market values. This type of research is descriptive quantitative. The data used was a medium-sized residential house as the object of valuation and three comparative data in the form of residential houses that have the same characteristics to find the market value of residential houses using the market approach. While in the cost approach, three comparative data of vacant land were used to find the land market value. This valuation resulted in a market value of IDR 3,009,000,000 which was obtained from the reconciliation of market values ​​in the market approach of IDR 3,175,529,000 and the cost approach of IDR 2,758,384,000. The liquidation value is set at 70% of the market value, which is IDR 2,106,000,000.